Columbia suicide severity rating scale screen scores in adults with Chiari malformation Type 1 - Richard Labuda; Emme Nolan; Emily P. Rabinowitz; Douglas L. Delahanty; Petra M. Klinge; Philip A. Allen (PLoS ONE, 2025)
Adult Chiari malformation Type 1 is a neurological condition characterized by high levels of chronic pain, disability, and psychological distress, yet self-harming behaviors have not previously been studied in this patient group. The purpose of this study was to determine the prevalence of elevated suicide risk scores among adults with Chiari malformation Type I using the Columbia Suicide Severity Rating Scale – Screen and examine the association between risk scores and pain, disability, and psychological distress. A web-based, anonymous survey was administered comprised of validated scales and demographic questions. Suicide risk (Columbia Screen score) was dichotomized as Low or High-Risk and both crude and adjusted odds ratios were calculated to determine statistical associations with pain, disability, and psychological measures. Overall, 44% of 372 respondents scored in the High-Risk group. Logistic regression showed that depression at the moderate level or above (Adjusted Odd Ratio (AOR) = 4.27, 95% CI = 2.58–7.05, p < .0001), age younger than 30 years (AOR = 3.10, 95% CI = 1.67–5.78, p = .0003), and severe or complete neck related disability (AOR = 2.02, 95% CI = 1.22–3.33, p = .0056) were significant predictors of High-Risk scoring. This study is the first to examine suicidal ideation and risk in the adult CMI population. Clinicians should be aware that suicidal ideation is a serious morbidity in this patient population.